Pengaruh Gelombang Ultrasonik pada Pembuatan Sabun Transparan dari Minyak Kelapa (Cocos nucifera) dan Minyak Ayam (Gallus domesticus) - Aman Santoso; Rohman Fantusi; Siti Marfu’ah; Sumari Sumari (Jurnal Teknik Kimia dan Lingkungan, 2021)
Transparent soap is synthesized from vegetable oils with alkaline bases through the saponification reaction with the addition of a transparent agent. The different material characteristics of coconut oil (Cocos nucifera) and chicken oil (Gallus domesticus) have the potential to produce unique transparent soap. Ultrasonic wave cavitation homogenizes the mixture and accelerates the reaction rate. The purpose of this research is to synthesize transparent soap from coconut oil and chicken oil and compared the soap produced using ultrasonic waves and with soap from the heating method. This experimental laboratory research was carried out with the stages of preparation and characterization of coconut oil and chicken oil, followed by saponification of coconut oil and chicken oil accompanied by ultrasonic waves. Characterization of the synthesized transparent soap. The results in this study indicate that soaps made from coconut oil are more transparent than those made from chicken oil, and soaps made with ultrasonic waves are more transparent than those made by normal heating. The ultrasonic transparent soap character of coconut oil has a moisture content of 22.02%, the non-saponified fraction 1.01%, insoluble part of alcohol by 1.79%, free alkaline by 0.04%, pH 9.35, and this is in accordance with SNI for soap except for its water content. Meanwhile, ultrasonic soap from chicken oil has a moisture content of 23.26%, non-saponified fraction 5.57%, the insoluble portion of alcohol was 4.69%, free alkaline 0.12%, pH 9.60, this is not in accordance with SNI soap. The soap produced by the ultrasonic method with coconut oil has the best character and has the most compatibility with SNI for solid soap.